2005
DOI: 10.1021/ma0474933
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Curing Behavior in Phase-Separated Structures

Abstract: Using time-resolved Fourier transform infrared spectroscopy, the reaction kinetics of ternary blends consisting of crystallizable polyester [poly(hexamethylene adipate) (PHMA)], polyether [poly(propylene glycol) (PPG)], and poly(methyl methacrylate-co-n-butyl methacrylate) [P(MMA-co-nBMA)] has been characterized. As the polyester and polyether have reactive isocyanate (NCO) units, they are able to react with water vapor in the environment. A specially designed cell was constructed to obtain reaction kinetics f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…An overtone of deformation vibration of NH group increased by Fermi resonance at 3185 cm K1 was also observed [29]. The conversion, r NCO of NCO groups was derived from the equation [23] …”
Section: Instruments and Cure Characterizationsmentioning
confidence: 96%
See 2 more Smart Citations
“…An overtone of deformation vibration of NH group increased by Fermi resonance at 3185 cm K1 was also observed [29]. The conversion, r NCO of NCO groups was derived from the equation [23] …”
Section: Instruments and Cure Characterizationsmentioning
confidence: 96%
“…For comparison purpose thick film (0.3 mm) of PTMG/TMP/TDI (NCO:OH ratio of 1.6:1) was also casted. The morphology of such PU-urea films significantly depends upon the film thickness [23], because the film Scheme 2. Two hydrogen bonded structure responsible for phase separation and phase mixing characteristics in the MCPU.…”
Section: Dsc Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 The morphology of IPNs has been characterized by optical microscopy, 19 scanning electron microscopy (SEM), 13,20 transmission electron microscopy, 21 and atomic force microscopy. 13,15,17,22 These studies have also shown that reaction conditions and sequence impact the final microstructure of IPNs.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, it must be taken into account that the final morphology also depends on the quenching processing conditions. Up to now, the research fields of solidification process mainly focused on metal materials and thermosetting resin composites [8, 9]. As for the latter, it mainly paid attention to the studies of curing reaction and its kinetic.…”
Section: Introductionmentioning
confidence: 99%